Pengaruh Transparansi Pengelolaan Keuangan terhadap Kepercayaan dan Partisipasi Anggota Koperasi Merah Putih - Doni Pratama Putra; Hendra Riofita (LPPM Politeknik Pratama, 2026)
This study aims to analyze the effect of financial management transparency on member trust and participation in Koperasi Merah Putih. Transparency is an important principle in good cooperative governance because it can influence the level of trust and active participation of members in cooperative activities. This study used a quantitative approach with a survey method. Data were collected through questionnaires distributed to 60 cooperative members selected using purposive sampling techniques. The research instrument used a Likert scale and was analyzed using descriptive and inferential statistical methods with the assistance of SPSS software. The results showed that the transparency of financial management in Koperasi Merah Putih was categorized as good, especially in terms of financial information disclosure and management accountability. The results of hypothesis testing indicated that financial management transparency had a positive and significant effect on member trust and member participation. In addition, member trust also had a positive effect on member participation in cooperative activities. However, several aspects still need improvement, particularly related to the accessibility and periodic delivery of financial reports. Therefore, cooperatives are expected to improve financial reporting systems, strengthen communication with members, and utilize digital media to support transparency and member participation.